Phenolic profile in the quality control of walnut (Juglans regia L.) leaves - Amaral, Joana S. (2004)
Qualitative and quantitative determinations of phenolic compounds were carried out on walnut leaves samples from six different cultivars, with the same agricultural, geographical and climatic conditions. The evolution of major phenolic compounds amounts was monitored from May to September. Two extractive procedures were assayed and best results were obtained using acidified water and a solid phase extraction column purification step. Qualitative analysis was performed by HPLC-DAD/MS and, in all samples, seven phenolic compounds were identified (3-caffeoylquinic, 3-p-coumaroylquinic and 4-p-coumaroylquinic acids, quercetin 3-galactoside, quercetin 3-arabinoside, quercetin 3-xyloside, quercetin 3-rhamnoside) and two other partially identified phenolics (quercetin 3-pentoside and kaempferol 3-pentoside derivatives) were also detected. Quantification of phenolic compounds was performed by HPLC-DAD, which revealed that quercetin 3-galactoside was always the major compound while 4-p-coumaroylquinic acid was the minor one. The highest content of phenolics was found in May and July.